Direct Ethanol Production from Lignocellulosic Materials by Mixed Culture of Wood Rot Fungi Schizophyllum commune, Bjerkandera adusta, and Fomitopsis palustris - Sakae Horisawa (Fermentation, 2019)
The cost of bioethanol production from lignocellulosic materials is relatively high because the additional processes of delignification and saccharification are required. Consolidated bioprocessing (CBP) simultaneously uses the multiple processes of delignification, saccharification, and fermentation in a single reactor and has the potential to solve the problem of cost. Some wood-degrading basidiomycetes have lignin- and cellulose-degrading abilities as well as ethanol fermentation ability. The white rot fungus Schizophyllum commune NBRC 4928 was selected as a strong fermenter from a previous study. The lignin-degrading fungus Bjerkandera adusta and polysaccharide-degrading fungus Fomitopsis palustris were respectively added to S. commune ethanol fermentations to help degrade lignocellulosic materials. Bjerkandera adusta produced more ligninase under aerobic conditions, so a switching aeration condition was adopted. The mixed culture of S. commune and B. adusta promoted direct ethanol production from cedar wood. Fomitopsis palustris produced enzymes that released glucose from both carboxymethylcellulose and microcrystalline cellulose. The mixed culture of S. commune and F. palustris did not enhance ethanol production from cedar. The combination of S. commune and cellulase significantly increased the rate of ethanol production. The results suggest that CBP for ethanol production from cellulosic material can be achieved by using multiple fungi in one reactor.